Revitalisasi Perpustakaan Sekolah dalam Meningkatkan Minat Baca Siswa di Sekolah Menengah Kejuruan Negeri 1 Percut SEI TUAN - Umara, Shoumi; Monang, Sori; Naldo, Jufri (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This study discusses the revitalization of the school library in increasing students' reading interest at SMK Negeri 1 Percut Sei Tuan. The purpose of this study was to determine the revitalization program at SMK Negeri 1 Percut Sei Tuan and how the impact of the revitalization program on students' reading interest. The research method uses a qualitative descriptive approach, using data collection techniques through interviews, observation and documentation. The informants used in this study were the Deputy Principal of the Facilities and Infrastructure School, the Head of the Library, Teacher and students at SMK Negeri 1 Percut Sei Tuan who had been selected by researchers according to the criteria of the research subject. Keywords: Revitalization, School Libraries, Reading